E-Module Helicopter Landing Officer Using Canva Platform - Ismail Husain, Taufik; Musadek, Ahmad; Silk Moonlight, Lady (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
One of the licenses that is quite much needed at this time is the Helicopter Landing Officer. Surabaya Aviation Polytechnic as one of the vocational institutions in the field of aviation provides HLO training. But until now, the unavailability of teaching materials that can be accessed by all training participants has become a challenge for Poltekbang Surabaya, so to create of teaching materials for Helicopter Landing Officer training and uploaded into the learning management system of Surabaya Aviation Polytechnic for the benefit of the training process. The e-module itself has several advantages over printed modules, including that it can more easily provide fast and automatic feedback for education and training participants. The process of preparing and testing the use of the HLO e-module, using the Research and Development method, where the method is devoted to the development of new products or adding functions to existing products. The process of preparing the HLO e-module was carried out using the ADDIE method (Analysis, Design, Development, Implementation, Evaluation). In the final result of the research, the preparation of the e-module has been successfully achieved and is included in the "feasible" category for material validation assessment, and "very feasible" for the response of training participants based on the results of data analysis from researchers. The research process has been in accordance with the initial research design and is expected to help the ongoing training process later.